Apomixis: genetic basis and controlling genes. Issue 1 (2nd July 2022) - Xu, Yuantao; Jia, Huihui; Tan, Chunming; Wu, Xiaomeng; Deng, Xiuxin; Xu, Qiang
Abstract: Apomixis is the phenomenon of clonal reproduction by seed. As apomixis can produce clonal progeny with exactly the same genotype to the maternal plant, it has important application value in genotype fixation and accelerating agricultural breeding strategies. Introduction of apomixis to major crops would bring many benefits to agriculture, including permanent fixation of superior genotypes, simplifying the procedures of hybrid seed production, as well as purification and rejuvenation of crops propagated vegetatively. Although apomixis naturally occurs in more than 400 plant species, it is rare among the major crops. Currently, with a better understanding of apomixis, some achievements have been made on synthetic apomixis. However, due to prevailing limitations, there is still a long way to large-scale application of apomixis for crop breeding. Here, we compare the developmental features of apomixis and sexual plant reproduction and review the recent identification of apomixis genes, transposons, epigenetic regulation and genetic events leading to apomixis. We also summarize the possible strategies and potential genes for engineering apomixis into crop plants.